2020
DOI: 10.1002/mame.202000679
|View full text |Cite
|
Sign up to set email alerts
|

Flaw Sensitivity and Tensile Fatigue of Poly(Vinyl Alcohol) Hydrogels

Abstract: Tensile fatigue behavior is commonly overlooked as researchers pursue the toughest hydrogels. This work describes a poly(vinyl alcohol) (PVA) hydrogel prepared through freezing–thawing (FT) processing to achieve varied monotonic strength and toughness. The monotonic tensile responses of relatively strong and weak versions of the hydrogel are studied with cylindrical hole and crack‐like flaws of different sizes to develop an understanding of monotonic strength in the presence of two different, extreme defect ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…As shown in Fig. S13 and S14 (ESI†), the CP/EGZn/betaine hydrogel electrolytes not only retained excellent mechanical properties under these demanding conditions, their qualitative behaviour is comparable to that of most existing PAAm gels, 50 alginate gels, 51 and PVA gels, 52,53 as well as DN gels 49 and zwitterion gels, 54 especially in terms of the fracture energy (Fig. S14, ESI†) and toughness (Fig.…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…As shown in Fig. S13 and S14 (ESI†), the CP/EGZn/betaine hydrogel electrolytes not only retained excellent mechanical properties under these demanding conditions, their qualitative behaviour is comparable to that of most existing PAAm gels, 50 alginate gels, 51 and PVA gels, 52,53 as well as DN gels 49 and zwitterion gels, 54 especially in terms of the fracture energy (Fig. S14, ESI†) and toughness (Fig.…”
Section: Resultsmentioning
confidence: 69%
“…It was found that the CP/EGZn/betaine hydrogel electrolyte with 0.6% CNF performed better in terms of tensile strength (70.3 kPa), Young's modulus (5.7 kPa), and toughness (61.6 kJ m À3 ) than that of P/EGZn/betaine hydrogel electrolyte, which is attributed to the reinforcement of the rigid CNF, bridging the PAA chains and the supramolecular betaine chains via H-bonds 2a and b show the stretching and compression process as well as the puncture resistance of the CP/EGZn/betaine hydrogels, respectively. (c) Comparison between this work and previous DN gels, 49 PAAm gels, 50 alginate gels, 51 PVA gels, 52,53 and zwitterion gels 54 in terms of fracture energy (Fig. S14, ESI †) and toughness.…”
Section: Mechanical Performancementioning
confidence: 85%
See 1 more Smart Citation
“…( F ) A mechanical properties space for soft materials; the two axes represent the fracture energy Г and the work to rupture W * , respectively, and the dashed line represents the fractocohesive length Г/ W * . The trehalose-modified PAAm hydrogels are compared with PAAm hydrogels, DN hydrogels ( 2 ), alginate hydrogels ( 55 ), PVA hydrogels ( 56 ), skin ( 57 ), natural rubbers ( 58 ), and polyurethane ( 46 ). ( G ) Trehalose-modified hydrogels with the edge cut are highly stretchable and exhibit flaw-tolerant capability.…”
Section: Resultsmentioning
confidence: 99%
“…Chemical cross‐linking may occur through various processes such as free‐radical polymerization, chemical agents and enzymatic reactions and high energy irradiation, which normally form covalent bridges between PVA polymer chains 3 . The crystalline nature of PVA is also of interest for forming crystalline zones as physical cross‐links network in a hydrogel, which can be developed by repeated simple freeze–thaw cycles 4 . In fact, such formed crystallites, that act as holding points within the network skeleton, distribute mechanical loads into gel structure and enhance its load‐bearing potential 5 …”
Section: Introductionmentioning
confidence: 99%